1995
DOI: 10.1037/0735-7036.109.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Manual laterality in chimpanzees (Pan troglodytes) in complex tasks.

Abstract: To determine the manual laterality of a sample of 24 chimpanzees, 4 problem apparatuses were used, the solution for which (obtaining a food item) required the use of 1 or both hands in sequential, simultaneous, or both sequential and simultaneous actions. The majority of the subjects showed significant and consistent hand preferences, especially in the actions that required a precision grip. The results obtained suggest the existence of factors linked to the specific characteristics of the task to be performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
38
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 29 publications
6
38
1
Order By: Relevance
“…Likewise, there is no significant hand preference at the population level even when a less stringent a 5 0.01 is used. Our results are in line with other NWM species (see Papademetriou et al [2005] for review) and are also consistent with other suborders which show no population bias toward lateralization of manual function (Prosimians [Cantalupo & Ward, 2000;Dodson et al, 1992;Sanford et al, 1984;Ward & Cantalupo, 1997;Ward et al, 1990]; OWM [Aruguete et al, 1992;Beck & Barton, 1972;Harigel, 1991;Rigamonti et al, 1998;Teichroeb, 1999;Westergaard et al, 2001]; and Apes [Byrne & Byrne, 1993;Colell et al, 1995;Hopkins et al, 1994;Rogers & Kaplan, 1996]). Our results are consistent with the notion that although some species show population level hand bias for specific activities, it is a uniquely human feature to show population level hand preference across a range of different behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, there is no significant hand preference at the population level even when a less stringent a 5 0.01 is used. Our results are in line with other NWM species (see Papademetriou et al [2005] for review) and are also consistent with other suborders which show no population bias toward lateralization of manual function (Prosimians [Cantalupo & Ward, 2000;Dodson et al, 1992;Sanford et al, 1984;Ward & Cantalupo, 1997;Ward et al, 1990]; OWM [Aruguete et al, 1992;Beck & Barton, 1972;Harigel, 1991;Rigamonti et al, 1998;Teichroeb, 1999;Westergaard et al, 2001]; and Apes [Byrne & Byrne, 1993;Colell et al, 1995;Hopkins et al, 1994;Rogers & Kaplan, 1996]). Our results are consistent with the notion that although some species show population level hand bias for specific activities, it is a uniquely human feature to show population level hand preference across a range of different behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Many have argued that populationlevel right-handedness is unique to human evolution and related to the emergence of gestural language, speech, tool use, and other higher cognitive functions (Bradshaw & Rogers, 1993;Corballis, 2002). However, recent studies in captive chimpanzees have reported evidence of population-level right-handedness for certain manual actions, including throwing, gestural communication, and coordinated bimanual actions (Colell, Segarra, & Sabater-Pi, 1995;Hopkins, 1995;Hopkins, Bard, Jones, & Bales, 1993;Hopkins & Cantalupo, 2003;Hopkins & Leavens, 1998;Wesley et al, 2002). These results challenge the long-held belief in the uniqueness of human right-handedness.…”
mentioning
confidence: 99%
“…This observation is particularly relevant in light of the recent evidence of taxonomic differences in functional asymmetries in nonhuman primates (see Corballis, 1992;Hopkins, 1996;Ward & Hopkins, 1993). For example, with specific reference to variations in hand preference, population-level right-handedness has been reported for coordinated bimanual actions in apes but not in New World monkeys (Colell, Segarra, & Sabater-Pi, 1995;Hopkins, 1995;Westergaard & Suomi, 1996); hand-preference data for coordinated actions in Old World monkeys have produced mixed results (Fagot & Vauclair, 1988;Westergaard, Champoux, & Suomi, 1997;Westergaard & Suomi, 1996). Regarding neuroanatomical asymmetries, great apes exhibit larger and more consistent left-occipital, right-frontal petalia asymmetries (LeMay, 1985) and have been reported to have a left-hemisphere asymmetry in sylvian fissure length, whereas monkeys do not (Yeni-Komshian & Benson, 1976; but see Heilbronner & Holloway, 1988).…”
mentioning
confidence: 99%